DINAMIKA EPIDEMIK TUBERCULOSIS (TB) PADA MODEL SATU STRAIN - Asep Solih Awalluddin (JURNAL ISTEK, 2011)
This paper explains mathematical model for dynamic of tuberculosis epidemic using one strain model, with supported theorems and lemmas. One strain model is elaborated in a condition of disease-free equilibrium and unique endemic equilibrium.